Ag-Catalyzed difluorohydration of β-alkynyl ketones for diastereoselective synthesis of 1, 5-dicarbonyl compounds. Issue 48 (15th May 2017) - Zhu, Yi-Long; Wang, Ai-Fang; Du, Jian-Yu; Leng, Bo-Rong; Tu, Shu-Jiang; Wang, De-Cai; Wei, Ping; Hao, Wen-Juan; Jiang, Bo
Abstract : A new catalytic difluorohydration of β-alkynyl ketones using NFSI as the fluorinating reagent has been established, diastereoselectively providing difluoride 1, 5-dicarbonyl products, and some of them were converted into difluorinated isoquinolines. Abstract : A new catalytic difluorohydration of β-alkynyl ketones using NFSI as the fluorinating reagent has been established, diastereoselectively furnishing a range of structurally diverse difluoride 1, 5-dicarbonyl products through C(sp 3 )–H fluorination. Notably, the sterically encumbered t -butyl functionality located at the α-position of the carbonyl group of substrates 1 showed excellent diastereoselectivity (up to >99 : 1 dr). The reaction enabled multiple bond-forming events including two C(sp 3 )–F formation through Ag-catalysis to provide a highly efficient and practical method toward difluoride 1, 5-dicarbonyls, some of which were successfully converted into difluorinated isoquinolines.